On the approximation by Chebyshev splines in the metric of L_p, p > 0 - Kryakin, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove a direct Jackson estimate for the approximation by Chebyshev splines in the classes L_p, p > 0.